2009
DOI: 10.24095/hpcdp.29.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Validity of autism diagnoses using administrative health data

Abstract: It is necessary to monitor autism prevalence in order to plan education support and health services for affected children. This study was conducted to assess the accuracy of administrative health databases for autism diagnoses. Three administrative health databases from the province of Nova Scotia were used to identify diagnoses of autism spectrum disorders (ASD): the Hospital Discharge Abstract Database, the Medical Services Insurance Physician Billings Database and the Mental Health Outpatient Information Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…We have nevertheless included them because this longitudinal study covers the transition from the DSM-4 to DSM-5 . Our case definition fits the one validated by Dodds et al 32…”
Section: Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…We have nevertheless included them because this longitudinal study covers the transition from the DSM-4 to DSM-5 . Our case definition fits the one validated by Dodds et al 32…”
Section: Methodssupporting
confidence: 57%
“…39 41 However, studies have shown that diagnoses recorded in medical records fully corresponded to entries in administrative databases for other diseases, in Quebec as in other provinces. 40,42 In addition, Dodds et al 32 reported that administrative health databases can clearly identify children with autism. Second, since QICDSS data only include information on people who use health care services, the case definition only identifies people who have received a diagnosis or treatment from a physician.…”
Section: Discussionmentioning
confidence: 99%
“…Only five conditions were investigated in more than one study: diabetes (10.6%) [ 13 - 16 ], inflammatory bowel disease (5.4%) [ 17 , 18 ], asthma (5.4%) [ 19 , 20 ], rotavirus infection (5.4%) [ 21 , 22 ], and tuberculosis (5.4%) [ 23 , 24 ]. However, a diverse range of conditions were investigated in single studies, including obesity [ 25 ], vaccine-related illness [ 26 ], injuries [ 27 ], autism [ 28 ], febrile neutropenia in oncology patients [ 29 ], high risk conditions [ 30 ], dermatologic conditions [ 31 - 33 ], congenital anomalies [ 34 ], cardiac defects [ 35 ], respiratory illnesses excluding asthma [ 36 - 38 ], neurologic conditions [ 39 ], other gastrointestinal conditions [ 40 - 43 ], genitourinary conditions [ 44 , 45 ], serum sickness [ 46 ], thrombosis [ 47 ], maternal/perinatal conditions [ 48 ], and drug-related anaphylaxis [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation of the administrative data usage is that the three health claim databases almost certainly did not capture all individuals who were diagnosed with ASDs during the study period. The sensitivity of the three databases has been previously reported as approximately 70% (Dodds et al, 2009). However, this estimate was not found to vary significantly based on several of the variables evaluated in the present study, including sex, birth order, birth weight, county of residence, maternal age, and the diagnosis of a major congenital anomaly.…”
Section: Discussionmentioning
confidence: 97%
“…Due to concerns regarding the reliability of diagnoses in children under the age of two years (Chawarska et al, 2007; Cox et al, 1999), those whose only ASD diagnostic code appeared before this age were excluded from the study. An earlier study reported the sensitivity and specificity of these data sources for detecting true cases of ASD as 69.3% and 77.3%, respectively (Dodds et al, 2009).…”
Section: Methodsmentioning
confidence: 99%